Potentiality of Achatina fulica Bowdich, 1822 (Mollusca: Gastropoda) as intermediate host of the Angiostrongylus costaricensis Morera & Céspedes 1971 - Omar dos Santos Carvalho; Horácio MS Teles; Ester Maria Mota; Cristiane Lafetá Gomes Furtado de Mendonça; Henrique Leonel Lenzi (Sociedade Brasileira de Medicina Tropical (SBMT), 2003)
Samples of Achatina fulica were experimentally infected with Angiostrongylus costaricensis larvae, etiological agent of abdominal angiostrongyliasis, showing that A. fulica is susceptible to the parasite. Achatina fulica may be a risk to urbanization of abdominal angiostrongyliasis presumably due to its high proliferation, continuous dispersion and remarkable adaptation in several Brazilian towns.